2013
DOI: 10.1186/bcr3445
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphisms in the circadian-related genes and breast cancer risk in Norwegian nurses working night shifts

Abstract: IntroductionSome studies have suggested that night work may be associated with an increased risk of breast cancer in nurses. We aimed to explore the role of circadian gene polymorphisms in the susceptibility to night work-related breast cancer risk.MethodsWe conducted a nested case-control study of Norwegian nurses comprising 563 breast cancer cases and 619 controls within a cohort of 49,402 Norwegian nurses ages 35 to 74 years. We studied 60 single-nucleotide polymorphisms (SNPs) in 17 genes involved in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 56 publications
2
72
1
7
Order By: Relevance
“…Additionally, it has been hypothesized that the increased risk of breast cancer among women working at night could be modulated by genetic polymorphisms in the circadian pathway genes. A few studies highlighted interactions between nightwork and specific circadian gene variants in relation to breast cancer (Monsees et al 2012, Grundy et al 2013, Zienolddiny et al 2013, but again none of the reported interactions were replicated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been hypothesized that the increased risk of breast cancer among women working at night could be modulated by genetic polymorphisms in the circadian pathway genes. A few studies highlighted interactions between nightwork and specific circadian gene variants in relation to breast cancer (Monsees et al 2012, Grundy et al 2013, Zienolddiny et al 2013, but again none of the reported interactions were replicated.…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation between expression level of core clock genes and breast cancer risk has been reported for the gene TIMLESS in peripheral blood lymphocytes of 80 breast cancer women compared with age-matched tumor-free equal cases [131]. Researchers have also discovered a significant association between number of successive night shifts and risk of breast cancer in women who have worked night shifts with single nucleotide polymorphism in the gene BMAL1 and related orphan receptor β (ROR-β), r [128]. The association between high risk of breast cancer and single nucleotide polymorphism in other core clock genes, such as BMAL2 and PER3 has been reported [128].…”
Section: Circadian Clock and Breast Cancermentioning
confidence: 99%
“…Researchers have also discovered a significant association between number of successive night shifts and risk of breast cancer in women who have worked night shifts with single nucleotide polymorphism in the gene BMAL1 and related orphan receptor β (ROR-β), r [128]. The association between high risk of breast cancer and single nucleotide polymorphism in other core clock genes, such as BMAL2 and PER3 has been reported [128].…”
Section: Circadian Clock and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…faktorer, men også biologiske prosesser i menneskekroppen: normal metabolisme (sto ski e), mikroora, in ammasjon, oksidativt stress og infeksjoner (Haugen 2015). Dette krever gode registre med demogra ske data og videre arbeid med identi kasjon av gode biomarkører for eksponering.…”
Section: Cancer In Norway 2015 -Special Issueunclassified